Analisis Hukum Terhadap Pencurian Data Administrasi Kependudukan Dalam Perspektif Undang-Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi - Kadek Ariesta Dwi Anggara; I Made Minggu Widyantara; I Wayan Kartika Jaya Utama (Fakultas Hukum Universitas Warmadewa, 2024)
Legal protection related to personal data has been legalized but raises norms of vagueness. So the formulation of the problem, 1) How is the security arrangement of population administration data according to law number 27 of 2022 concerning personal data protection? and 2) How is the form of legal protection for the theft of population administration data in Indonesia. Using normative research methods. The results showed that the Personal Data Protection Law is still not maximized in its application, so it is still multi-interpretive in article 67 paragraph (2). The lack of clarity of the phrase